Effects of agroforestry land use on microclimate modification and productivity in dry areas - Singh, G.; Singh, Bilas; Rathore, T.S. (Indian Journal of Agroforestry, 2020)
Various types of agroforestry systems exist in dry areas involving forest trees, horticultural trees, agriculture crops, grasses, and animals. By linking forests and agriculture, agroforestry provides ecosystem services and environmental benefits at both regional and global level. Improvement in air, water and soil quality; carbon sequestration; and biodiversity conservation are the major benefits. Interactions among different components of an agroforestry system may be complementary, supplementary or competitive depending upon the stages of growth, types of species, tree age, rooting patterns and most importantly availability of resources like soil water, nutrients and light. Synergistic effects of woody component can beneficially be utilized and negative effects minimized by adopting suitable management practices like tree canopy removal, tree thinning, root pruning, fertilization etc to enhance productivity of companion crop/vegetation. This manuscript describes the beneficial effects of agroforestry as compared to forests and agriculture including microclimate modification and soil improvement putting major emphasis on desert ecosystem.